Pneumoperitoneum due to sigmoid tension perforation - Cassinelli, Daniel; Galarraga, José (Cirugía del Uruguay, 1975)
The case of a hypertensive pneumoperitoneum in an aged female patient who was suffering from peritonitis caused by a sigmoid perforation, is described. The most remarkable clinical symptom was abdominal distention, which retarded making correct diagnosis, with ultimate fatal development. Emphasis is placed on the fact that this particular form of sigmoid perforation is unusual and that abdominal symptomatology is very scanty in aged persons with peritonitis.